Celio-mesenteric and Leriche syndrome: Treatment for aorto-bifemoral-mesenteric bypass - Danza, Rómulo; Navarro, Teodoro; Baldizán, Jorge (Cirugía del Uruguay, 1982)
A 51 years-old patient presenting a Leriche syndrome associated with a serious intestinal angor is presented. Proper arteriographies showed lesions common to the Leriche syndrome with the obstruction of the celiac trunk and superior mesenteric artery in its origin. There was an abscence of the inferior mesenteric arteriogram. This lesional association is not common. The importance of an early diagnose - clinical and arteriographic- of the mesenteric lesions to avoid its final and fatal complication (intestinal infarction) is underlines. Surgical treatment requires a complex revascularisation (Aortobifemoral bypass + Prosthesic-mesenteric bypass). Postoperatory evolution was excellent with dissapearance of the digestive and legs symtomathology, with an evident increase of corporal weight.